Verification of the 3D capability of OpenMOC with the C5G7 3D extension benchmark. (1st June 2020) - Wu, Wenbin; Yu, Yingrui; Luo, Qi; Yao, Dong; Li, Qing; Chai, Xiaoming
Highlights: The C5G7 3D problems are solved for the verification of the 3D transport capability of OpenMOC. The base solutions for all three configurations agree well with the benchmark reference. Sensitivity investigations of the MOC parameters and the acceleration parameters are carried out. Abstract: Due to its numerical accuracy, geometrical flexibility, potential parallel degrees, and implementary simplicity, the Method of Characteristics (MOC) is a very promising candidate for high-fidelity full-core transport solving. OpenMOC, a general purpose open source neutron transport solver, was originally a 2D criticality calculation solver, and has been extended to have 3D capability recently. This paper presents the solutions obtained with OpenMOC to the C5G7 3D extension benchmark problems along with the sensitivity analysis of simulation parameters. All three configurations are calculated, and the results are compared with the benchmark reference with respect to both the multiplication factor and the pin power distribution. Good agreements with the reference results were reached, verifying the solution accuracy of the 3D capability of OpenMOC.